Características de la oferta hídrica de la Microcuenca Rumiyacu-Mishquiyacu para uso potable en la ciudad de Moyobamba 2004-2005 - Zumaeta Soplín, Anselma (2005)
SWAT MODEL allowed to georeferenciar the affluents of the micro river basin, to identify units of hydrological answer, to determine the water production, the contribution of sediments to the volume by each unit of hydrological answer and to calculate the simulated volume. ArcView 3.3, allowed to develop the ground map, earth use, units of hydrological answer and the location of the affluentes of the micro river basin. Also, it was made gaugings to determine the water real volume and to elaborate the calibration chart of the same one, from the registries of the height of the water lamina, that were made with limnimetro that settled in micro river basin. In the save way, a rain gauge settled with the precipitation fallen during a year in micro was registered river basin. For the water bacteriological analysis the method of filtration by membrane was used, that allowed to determine the present concentration of coliform totals and fecales in the water that attracts to supply to the population of Moyobamba city. Also the chemical physical parameters like the Turbidity, Dissolved Total Solids, Hardness, Chlorides, Sulphates, pH and other were analyzed that are detailed within the present work.